A novel Sm3+-activated Li3BaSrLn3(MO4)8 [Ln = La, Gd, and Y; M = Mo and W] deep red-emitting phosphors for plant cultivation and white LEDs. Issue 2 (3rd April 2021) - Rajendran, Marikumar; Singh, Kasturi; Vaidyanathan, Sivakumar
Abstract : Deep red phosphor-based LEDs play a crucial role in plant growth applications, where the LED emission covers the phytochrome (Pr) absorption. In this context, a series of Sm 3+ -activated Li3 BaSrLn3 (MO4 )8 :Sm 3+ [Ln = La Gd and Y; M = Mo and W] deep red phosphors were synthesized using the solid-state method. The outcome of the PXRD patterns suggests that the synthesized phosphors were crystallized in a monoclinic structure with the space group C2/c. SEM analysis was executed to study the morphology of the phosphors, and an FT-IR study was performed to study the stretching frequency of the MO/W-O bond in the (Mo/W)O4 groups. All the Sm 3+ -activated phosphors showed intense emission at 646 nm due to their 4 G5/2 → 6 H9/2 transition and exhibited excellent thermal stability (> 72% at 423K). The selected phosphors showed internal quantum efficiency at around 30%. The pc-LEDs were fabricated with the combination of near-UV LED and the synthesized deep-red phosphors. Besides, the emission spectrum of the fabricated LED was compared with the phytochrome Pr absorption spectrum for de plant growth application. These results suggest that the synthesized phosphor can be useful in the white LED fabrication to improve the CRI and can also be beneficial in the plant growth field.